Ownership Structure and Bankruptcy: The Effect of Audit Committee Size - Garba, Sunusi; Mohamed, Mudzamir Bin (International Journal of Engineering and Technology, 2018)
This paper analyses the interactive role of audit committee size on the link concerning ownership structure and bankruptcy. The study uses the listed Nigeria financial firms’ yearly reports from 2006 to 2015. The sample comprises of twenty-nine (29) quoted firms. Estimation was used with Driscoll and Kraay’s standard errors. The findings establish that executive, non-executive directors, and institutional ownership have a positive influence on Altman Z-score that is having lower bankruptcy possibilities. However, CEO, block and foreign ownership were found to have a negative influence on Altman Z-score that is having higher bankruptcy possibilities. The effective audit committee overturns these inverse relationships. Hence found that audit committee size moderates CEO, block and foreign ownership relationship with Altman Z-score positively. However, audit committee size moderates the effects of executives and institutions ownership on the Altman Z-score negatively and significantly. It is recommended that regulators should impose practical regulations to lessen the power of executives and institutional investors over the audit committee size in order to protect the interests of the minority shareholders.